2015
DOI: 10.1371/journal.pone.0126609
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acute HIV-1 Infection by RT-LAMP

Abstract: A rapid, cost-effective diagnostic test for the detection of acute HIV-1 infection is highly desired. Isothermal amplification techniques, such as reverse-transcription loop-mediated isothermal amplification (RT-LAMP), exhibit characteristics that are ideal for the development of a rapid nucleic acid amplification test (NAAT) because they are quick, easy to perform and do not require complex, dedicated equipment and laboratory space. In this study, we assessed the ability of the HIV-1 RT-LAMP assay to detect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…The primary goal of the current study was to demonstrate the performance of a prototype single-use, electricity-free heating device for the detection of HIV-1 by RT-LAMP. Previously, it has been demonstrated that the HIV-1 RT-LAMP assay can reduce the window of detection between infection and seroconversion (Rudolph et al, 2015). The results from this study demonstrate a step forward towards the development of a single-use, rapid NAT that may supplement rapid antibody testing at the POC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary goal of the current study was to demonstrate the performance of a prototype single-use, electricity-free heating device for the detection of HIV-1 by RT-LAMP. Previously, it has been demonstrated that the HIV-1 RT-LAMP assay can reduce the window of detection between infection and seroconversion (Rudolph et al, 2015). The results from this study demonstrate a step forward towards the development of a single-use, rapid NAT that may supplement rapid antibody testing at the POC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the temperature of the NINA-SUD devices began to decline from the optimal 60°C reaction temperature prior to the completion of the 60 minute amplification step, initial validation studies indicated that the majority of all amplification reactions occur within 30 minutes (data not shown). Importantly, all clinical specimens were detected within the reported limit of detection of the assay for RNA, which is 10 4 copies/mL (Rudolph et al, 2015). Since the RT-LAMP reaction can amplify from RNA, as well as DNA targets, the contribution from proviral DNA cannot be excluded and may explain amplification of specimens with a VL <10 4 RNA copies/mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations